Curriculum Implementation Planning on The Tactical Assembly of Diniyah Conversion (MTKD) in The City of Bandung - Yustina Yuliasari (UIN Sunan Gunung Djati Bandung, 2020)
The curriculum as an educational design has a fairly central position in all educational activities, determining the implementation process and educational outcomes. Given the important role of the curriculum in education and in the development of human life, curriculum preparation cannot be done carelessly. Sukmadinata emphasized that curriculum preparation requires strong foundations, which are based on the results of in-depth thought and research. Planning for curriculum implementation is carried out by compiling a curriculum that is tailored to the needs and level of knowledge of the congregation, then determining the curriculum concept to be applied, the methods to be used and the learning strategies to be implemented. The curriculum team compiles learning materials and divides learning materials into semester, monthly and material in each meeting.